Experimental evolution with yeast - Zeyl, Clifford (FEMS yeast research, 2006)
Many of the difficulties of studying evolution in action can be surmounted using populations of microorganisms, such as yeast. A readily manipulated sexual system and an increasingly sophisticated array of molecular and genomic tools uniquely qualify Saccharomyces cerevisiae as an experimental subject. This minireview briefly describes some recent contributions of yeast experiments to current understanding of the evolution of ploidy, sex, mutation, and speciation.